A physically-based model considering dislocation–solute atom dynamic interactions for a nickel-based superalloy at intermediate temperatures. (5th December 2019) - Lin, Y.C.; Yang, Hui; He, Dao-Guang; Chen, Jian
Abstract: The uniaxial tensile tests are performed to study flow behavior of a nickel-based superalloy with different initial microstructures at an intermediate temperature range (473–973 K). The experimental results show that the obvious serrated flow characteristics can be observed from the flow stress curves. Meanwhile, it is concluded that the occurrence of serrated flow features not only associate with deformation parameters, but also are prominently influenced by different initial microstructures. Furthermore, based on the plastic deformation mechanism of the investigated superalloy and dislocation-solute atoms dynamic interactions, a physically-based constitutive model is developed. The dynamic characteristics of the developed model are discussed, i.e., the evolution of moving dislocation, solute atoms concentration, and the strain rate dependent stress are analyzed. Additionally, various types of serrations are numerically simulated by appropriate parameters. Also, the predicted results show a good coincident with the observed data, suggesting that the established model can accurately describe the intermediate-temperature flow behaviors involving the serrated flow features of the investigated nickel-based superalloy. Graphical abstract: Unlabelled Image Highlights: Serrated flow features of a nickel-based superalloy with different initial microstructures were study. Serrated flow features are prominently influenced by deformation parameters and initial microstructures. A physically-based constitutive model is developed considering dislocation-solute atoms dynamic interactions. The evolution of moving dislocation, solute atoms concentration, and the strain rate dependent stress are analyzed. The established model can well described the intermediate-temperature the serrated flow features.